Estimation of Methane Emissions using the IPCC FOD Model with Local Parameters and Mitigation Analysis - Ni Ketut Nadia Mahadewi; I Made Gunamantha; I Ketut Sudiana (LifeSciFi, 2026)
The increasing generation of urban waste dominated by organic materials has contributed to increased methane emissions. The objectives of this study were to estimate CH₄ emissions, analyze the influence of waste composition, and develop mitigation scenarios based on the IPCC First Order Decay approach with local parameters. The method used was a quantitative descriptive study using the IPCC 2006 FOD model calibrated with waste generation and composition data for 2015–2024, complemented by sensitivity analysis and simulation of landfill gas management scenarios. The results showed that methane emissions increased cumulatively from 1.12 to 5.14 Gg CH₄/year, influenced by the dominance of the organic fraction of 60–65% and anaerobic landfill conditions without a gas capture system. Scenario analysis showed that mitigation strategies such as flaring, waste-to-energy, and bioreactors were able to reduce emissions by more than 60% compared to business-as-usual conditions. In conclusion, methane emissions are strongly influenced by the amount and composition of waste, as well as the effectiveness of landfill management